1984
DOI: 10.1029/jb089ib06p04137
|View full text |Cite
|
Sign up to set email alerts
|

Subcritical crack growth and other time‐ and environment‐dependent behavior in crustal rocks

Abstract: Stable crack growth strongly influences both the fracture strength of brittle rocks and some of the phenomena precursory to catastrophic failure. Quantification of the time and environment dependence of fracture propagation is attempted with the use of a fracture mechanics technique. We examine some of the difficulties encountered when applying techniques originally developed for simple synthetic materials to complex materials like rocks. A picture of subcritical fracture propagation is developed that embraces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
78
0
3

Year Published

1988
1988
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 187 publications
(93 citation statements)
references
References 40 publications
12
78
0
3
Order By: Relevance
“…The author shows a photograph of a vein and alteration halo for a crack that apparently has slowed down and finally come to arrest, resulting in a continuously decreasing size of both the width of the alteration zone and the width of the vein itself. Furthermore, in laboratory acoustic emission measurements, Swanson (1984) found that the activity in the process zone occurred closer to the crack surfaces and at lower rates when the crack speed was reduced.…”
Section: A Mechanical Model For the Development Of The Damage Zone Anmentioning
confidence: 99%
“…The author shows a photograph of a vein and alteration halo for a crack that apparently has slowed down and finally come to arrest, resulting in a continuously decreasing size of both the width of the alteration zone and the width of the vein itself. Furthermore, in laboratory acoustic emission measurements, Swanson (1984) found that the activity in the process zone occurred closer to the crack surfaces and at lower rates when the crack speed was reduced.…”
Section: A Mechanical Model For the Development Of The Damage Zone Anmentioning
confidence: 99%
“…Brittle fracture strength is influenced by environmental factors such as relative humidity and chemical reactivity that can weaken the bonds between material grains Swanson, 1984). For instance, most rock and ceramic material exhibit maximum fracture resistance (termed critical fracture toughness) when tested in a vacuum, and that strength is significantly reduced in the presence of water or water vapor.…”
Section: Subcritical Crack Growthmentioning
confidence: 99%
“…Fracture propagation below the critical toughness, termed subcritical crack propagation, occurs at lower stress levels and much lower velocities. A useful attribute of subcritical crack growth is that propagation velocity, v, can be related to opening mode stress intensity at the crack tip, K I , with an empirically quantifiable, power-law relationship Swanson, 1984;Olson, 1993),…”
Section: Subcritical Crack Growthmentioning
confidence: 99%
“…The factor c and the exponent /• are material dependent; for rocks • tends to be about 100 [Swanson 1984, Atkinson 1984]. …”
Section: Microcracksmentioning
confidence: 99%